METHOD AND SOFTWARE OPTIMIZATION DISTRIBUTION OF INFORMATION FILES IN COMPUTER NETWORKS - Zhukov , I. A.; Ivankevich, A. V.; Shibani, Salim Al; Al-Suriki, Ibrahim (Problems of Informatization and Control, 2021)
A method is proposed for the optimal distribution of information files over the nodes of a computer network when transferring large amounts of data. The features of increasing the productivity of universal multiservice networks when using software to optimize the load of network nodes are investigated.